Edukasi Deteksi Dini Kanker Serviks Di Desa Bangun Rejo Tahun 2024 - Astaria Br Ginting; Ade Rachmat Yudiyanto; Cris Anggelina Br Manik; Deby Febriani Saputri (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Cervical cancer is the most common cancer in Indonesia. Cancer has a high mortality rate caused by delays in diagnosis and treatment. Nearly 70% of cancer patients are detected at an advanced stage. This is very unfortunate, because cervical cancer can be found at a stage before cancer occurs (precancerous lesions) which can be treated so that it does not become cancer. The early detection program for cervical cancer in Indonesia is carried out using the Acetic Acid Visual Inspection (IVA) method carried out by trained health workers. In three years (2020-2022), as many as 3,914,885 women aged 30-50 years or 9.3% of the target have undergone early detection of cervical cancer using the IVA method. The highest early detection of targets has undergone early detection of cervical cancer using the IVA method. Early detection was reported by West Nusa Tenggara Province at 34.1%, followed by South Sumatra at 33.5%, and Bangka Belitung Islands at 27.8%. Meanwhile, the province with the lowest early detection coverage is Papua at 0.1%, followed by West Papua at 0.4%, and North Sulawesi at 0.7%. In 2022, of the 2,175,314 women aged 30-50 years who had early detection of cervical cancer, 7,869 (0.36%) had positive VIA examination results and 1,232 (0.06%) were suspected of cervical cancer.